Leplayowskie inspiracje w socjologii polskiej = Le Play`s influence on Polish sociology - Wincławski, Włodzimierz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
For the first time Le Play was mentioned in Polish writing in 1860 by Ludwik Górski. The author used Le Play`s monographic method from "Les ouvriers Europeens" (1855) to describe the conditions of country workers in Poland. Górski did not find followers because of the 1863 uprising. Le
Keywords: Le Play, Frédéric (1806-1882); metoda monograficzna; socjologia; badania socjologiczne; Francja; 19 w.